Solid electrolyte material and preparation method thereof, positive electrode active material and preparation method thereof, positive electrode sheet, battery and electrical equipment

By adjusting the diffraction peak 2θ value of LiTi2(PO4)3 in the solid electrolyte material with NASICON crystal structure, broadening the transmission channel of lithium ions, solving the problem of low ion conductivity of existing solid electrolyte materials, and improving the battery rate performance.

CN118610560BActive Publication Date: 2025-04-22BEIJING EASPRING MATERIAL TECH CO LTD

Patent Information

Application Number
CN202410814749.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-04-22
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

The ionic conductivity of existing solid electrolyte materials is low, which affects the rate performance and cycling performance of the battery.

Method used

The solid electrolyte material with NASICON crystal structure broadens the transmission channel of lithium ions by reducing the 2θ value of the diffraction peak in the standard pattern of LiTi2(PO4)3 by 0.02°-0.06°, thereby improving the ion conductivity.

Benefits of technology

The ionic conductivity of the solid electrolyte material is significantly improved, so that the cells containing it have excellent rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118610560B_ABST
    Figure CN118610560B_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte material and a preparation method thereof, a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device, and relates to the field of battery technology. The solid electrolyte material is a NASICON crystal structure, and in the X-ray diffraction spectrum of the solid electrolyte material, the 2θ value representing the diffraction peak of LiTi2(PO4)3 is reduced by 0.02°-0.06° compared to the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3. Thus, the use of the solid electrolyte material can make the battery loaded with it have excellent rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and specifically relates to a solid electrolyte material and a preparation method thereof, a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] Range anxiety and battery safety issues have become the pain points and major bottlenecks that restrict the development of new energy vehicles. The key to the iterative innovation of the next generation of higher energy density and safer power batteries lies in the technological breakthrough of solid-state batteries. As the core material of solid-state batteries, the comprehensive performance and industrialization progress of solid-state electrolyte materials are the key to the development of solid-state batteries. At present, solid-state electrolyte materials with industrialization prospects mainly include three major systems: polymers, sulfides and oxides. Among them, although sulfide electrolytes have high conductivity, they have high manufacturing costs and unstable structures, and large-scale production and loading face huge challenges; polymer solid electrolytes are soft and easy to process, but have low room temperature ionic conductivity and cannot tolerate voltages above 4.0V; NASICON oxide solid electrolytes have stable structures, low costs, and high voltage windows, and are easy to iterate from semi-solid, quasi-solid, to all-solid batteries. However, the ionic conductivity of oxide solid electrolytes is still lower than that of electrolytes, which affects the rate performance and cycle performance of batteries. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a solid electrolyte material and a preparation method thereof, a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device, wherein the solid electrolyte material has high ionic conductivity, so that the battery containing the solid electrolyte material has excellent rate performance.

[0004] In one aspect of the present invention, a solid electrolyte material is provided, wherein the solid electrolyte material is a NASICON crystal structure, and in the X-ray diffraction spectrum of the solid electrolyte material, the 2θ value of the diffraction peak representing LiTi2(PO4)3 is reduced by 0.02°-0.06° compared to the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3.

[0005] According to the solid electrolyte material of an embodiment of the present invention, the 2θ value of the diffraction peak representing LiTi2(PO4)3 is reduced by 0.02°-0.06° compared with the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3, thereby increasing the unit cell parameters and unit cell volume of the solid electrolyte material. As a result, the transmission channel of lithium ions is widened, the ionic conductivity of the solid electrolyte material can be improved, and the battery containing the same has excellent rate performance.

[0006] In addition, the solid electrolyte material according to the above embodiment of the present invention may also have the following additional technical features:

[0007] In some embodiments of the present invention, the diffraction peaks representing LiTi2(PO4)3 include diffraction peak (012), diffraction peak (104), diffraction peak (113) and diffraction peak (024). Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0008] In some embodiments of the present invention, the unit cell parameters of the solid electrolyte material are compared with the unit cell parameters of LiTi2(PO4)3, and the a value is increased. The c value increases Thereby, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0009] In some embodiments of the present invention, the unit cell volume of the solid electrolyte material is increased compared to the unit cell volume of LiTi2(PO4)3. Thereby, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0010] In some embodiments of the present invention, the X-ray diffraction spectrum of the solid electrolyte material has a diffraction peak (721) at a diffraction angle 2θ value of 27.7°-27.8°, the peak intensity of the diffraction peak (721) is I1, the peak intensity of the diffraction peak (113) is I2, and 0.1≤I1 / I2≤0.5. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0011] In some embodiments of the present invention, the ionic conductivity of the solid electrolyte material is greater than or equal to 5×10 - 4 S / cm, can be selected to be greater than or equal to 1×10 -3 Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0012] In some embodiments of the present invention, the average particle size of the solid electrolyte material is 0.05 μm-0.5 μm, preferably 0.05 μm-0.1 μm. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0013] In some embodiments of the present invention, at 25 °C, the pH value of the solid electrolyte material is 6-10. Thereby, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0014] In some embodiments of the present invention, the solid electrolyte material includes:

[0015] Li x M 1 y M 2 z Ti u (PO4) v1 (P2O7) v2 ,

[0016] wherein, M 1 includes at least one of the first main group elements other than Li, and M 2 includes at least one of the metal elements with a positive trivalent valence, 1≤x<4, 0.1≤y≤0.5, 0.2<z≤0.5, 1<u≤5.5, 2≤v1≤6, 0.1<v2≤3. Thereby, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0017] In some embodiments of the present invention, M 1 includes at least one of K, Rb, and Cs. Thereby, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0018] In some embodiments of the present invention, M 2 includes at least one of V, La, and Cr. Thereby, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0019] In the second aspect of the present invention, the present invention provides a method for preparing the above-mentioned solid electrolyte material, including:

[0020] Mixing the M 2 source, Ti source, PO4 3- source, P2O7 4- source, precipitant, and solvent, and obtaining a precursor through coprecipitation and filtration;

[0021] Mixing the precursor with the Li source and M 1 source, and sintering in an oxygen-containing atmosphere to obtain the solid electrolyte material.

[0022] Thus, the above-mentioned solid electrolyte material can be prepared by this method, and pyrophosphate is introduced into the unit cell of the conventional LiTi2(PO4)3 structure, and the doping element M 1 and M 2 , which increases the unit cell parameters and unit cell volume, thereby widening the lithium ion transmission channel, which can improve the ionic conductivity of the solid electrolyte material and make the battery containing it have excellent rate performance.

[0023] In some embodiments of the present invention, the oxygen-containing atmosphere includes oxygen or air. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0024] In some embodiments of the present invention, the sintering temperature is 600° C.-800° C., and the sintering time is 4 h-10 h. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0025] In some embodiments of the present invention, the M 1 Sources include M 1 Oxides containing M 1 Phosphate, containing M 1 Sulfate, containing M 1 Chloride, containing M 1 Nitrate and M 1 Thereby, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0026] In some embodiments of the present invention, the M 2 Sources include M 2 Oxides containing M 2 Phosphate, containing M 2 Sulfate, containing M 2 Chloride, containing M 2 Nitrate and M 2 Thereby, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0027] In some embodiments of the present invention, the Ti source includes at least one of a phosphate containing Ti, an acetate containing Ti, a sulfate containing Ti, a chloride containing Ti, a nitrate containing Ti, and a carbonate containing Ti. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0028] In some embodiments of the present invention, the PO4 3- The source includes at least one of H3PO4, NH4H2PO4, (NH4)2HPO4, (NH4)3PO4, LiH2PO4, Li2HPO4, Li3PO4, NaH2PO4, Na2HPO4, and Na3PO4. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0029] In some embodiments of the present invention, the Li source includes at least one of lithium carbonate, lithium hydroxide, and lithium nitrate. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0030] In some embodiments of the present invention, the P2O7 4- The source includes at least one of H4P2O7, (NH4)2H2P2O7, Li2H2P2O7, and Li4P2O7. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing it has excellent rate performance.

[0031] In some embodiments of the present invention, the precipitant includes at least one of sodium hydroxide, sodium carbonate, and ammonia water. Thus, the ionic conductivity of the solid electrolyte material can be further improved, so that the battery containing the solid electrolyte material has excellent rate performance.

[0032] In the third aspect of the present invention, the present invention provides a positive electrode active material, the positive electrode active material comprises a substrate and a coating layer provided on at least part of the surface of the substrate, the coating layer comprises the solid electrolyte material described in the first aspect of the present invention or the solid electrolyte material prepared by the method described in the second aspect. Thus, the surface of the positive electrode active material is coated with the solid electrolyte material, the solid electrolyte material introduces pyrophosphate into the unit cell of the conventional LiTi2(PO4)3 structure, and the doping element M 1 and M 2 , which increases the unit cell parameters and unit cell volume, thereby widening the lithium ion transmission channel, which can improve the ionic conductivity of the positive electrode active material, so that the battery containing it has excellent rate performance.

[0033] In some embodiments of the present invention, the coating layer has a thickness of 10 nm-500 nm, thereby the prepared positive electrode active material has high ion conductivity, so that the battery containing the positive electrode active material has excellent rate performance.

[0034] In some embodiments of the present invention, based on the total mass of the positive electrode active material, the mass proportion of the solid electrolyte material is 0.01%-1%. Thus, the prepared positive electrode active material has high ion conductivity, so that the battery containing it has excellent rate performance.

[0035] In some embodiments of the present invention, in the DSC test curve of the positive electrode active material, the temperature corresponding to the exothermic peak is ≥ 220° C. Thus, the prepared positive electrode active material has high ion conductivity, so that the battery containing it has excellent rate performance.

[0036] In some embodiments of the present invention, the matrix includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, lithium manganese phosphate and lithium manganese iron phosphate, thereby, the prepared positive electrode active material has high ionic conductivity, so that the battery containing it has excellent rate performance.

[0037] In a fourth aspect of the present invention, the present invention provides a method for preparing the positive electrode active material according to the third aspect, comprising:

[0038] Grinding the solid electrolyte material into nanoparticles and mixing the nanoparticles with a matrix to obtain a mixed material;

[0039] The mixed material is heat-treated in an oxygen-containing atmosphere to obtain a positive electrode active material.

[0040] Thus, the positive electrode active material prepared includes a substrate and a coating layer provided on at least part of the surface of the substrate, wherein the coating layer includes the solid electrolyte material described in the first aspect of the present invention or the solid electrolyte material prepared by the method described in the second aspect. Thus, the surface of the positive electrode active material is coated with the solid electrolyte material, and the solid electrolyte material introduces pyrophosphate into the unit cell of the conventional LiTi2(PO4)3 structure, and the doping element M 1 and M 2 , which increases the unit cell parameters and unit cell volume, thereby widening the lithium ion transmission channel, which can improve the ionic conductivity of the solid electrolyte material and make the battery containing it have excellent rate performance.

[0041] In some embodiments of the present invention, the oxygen-containing atmosphere comprises oxygen or air;

[0042] Optionally, the temperature of the heat treatment is 300° C.-500° C., and the time of the heat treatment is 2 h-8 h.

[0043] Thus, the prepared positive electrode active material has high ion conductivity, so that the battery containing it has excellent rate performance.

[0044] In a fifth aspect of the present invention, the present invention provides a positive electrode plate, comprising the positive electrode active material described in the third aspect of the present invention, or the positive electrode active material prepared by the method described in the fourth aspect.

[0045] In the sixth aspect of the present invention, the present invention provides a battery, comprising at least one of the solid electrolyte material described in the first aspect of the present invention, the solid electrolyte material prepared by the method described in the second aspect, and the positive electrode sheet described in the fifth aspect. Thus, the battery has excellent electrochemical performance.

[0046] In the seventh aspect of the present invention, the present invention provides an electrical device, comprising the battery described in the sixth aspect of the present invention.

[0047] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is the XRD diagram of the solid electrolyte material of Comparative Example 1 and Examples 1-4 of the present application at a 2θ value of 10°-70°;

[0049] Figure 2 It is the XRD diagram of the solid electrolyte material of Comparative Example 1 and Examples 1-4 of the present application at a 2θ value of 10°-30°;

[0050] Figure 3 This is a SEM image of the solid electrolyte material of Example 1 of the present application. DETAILED DESCRIPTION

[0051] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0052] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0053] In one aspect of the present invention, a solid electrolyte material is provided, wherein the solid electrolyte material is a NASICON crystal structure, and in the X-ray diffraction spectrum of the solid electrolyte material, the 2θ value of the diffraction peak representing LiTi2(PO4)3 is reduced by 0.02°-0.06° compared to the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3.

[0054] As an example, the 2θ value of the diffraction peak representing LiTi2(PO4)3 can be reduced by 0.02°, 0.03°, 0.04°, 0.05°, 0.06°, etc. compared to the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3 (PDF#35-0754).

[0055] It can be understood that in the X-ray diffraction spectrum of the solid electrolyte material, there can be one or more diffraction peaks representing LiTi2(PO4)3. When there are multiple diffraction peaks, the corresponding 2θ value of each diffraction peak is reduced by 0.02°-0.06° compared with the diffraction peak at the corresponding position in the standard spectrum. In addition, when there are multiple diffraction peaks, when only one diffraction peak is compared with the diffraction peak at the corresponding position in the standard spectrum, the corresponding 2θ value is reduced by 0.02°-0.06°, or when not all diffraction peaks are compared with the diffraction peaks at the corresponding position in the standard spectrum, the corresponding 2θ value is reduced by 0.02°-0.06°, it is also within the scope of protection of the present application.

[0056] The inventors found that when the 2θ value of the diffraction peak representing LiTi2(PO4)3 in the X-ray diffraction spectrum of the solid electrolyte material is 0.02°-0.06° less than the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3. According to the Bragg equation 2dsinθ=nλ, for X-ray diffraction, when the optical path difference is equal to an integer multiple of the wavelength, the diffraction line of the crystal plane will be strengthened, where d is the crystal plane spacing, θ is the angle between the incident line, the reflected line and the reflected crystal plane, λ is the wavelength, and n is the reflection order. When the detection wavelength is fixed, the decrease in the 2θ value means that the crystal plane spacing d value increases, and the corresponding unit cell parameters and volume will also increase accordingly. Therefore, the crystal of the solid electrolyte material obtained is compared with the standard LiTi2(PO4)3 crystal, and the unit cell parameters and unit cell volume are increased. As a result, the transmission channel of lithium ions is widened, which can improve the ionic conductivity of the solid electrolyte material, so that the battery containing it has excellent rate performance.

[0057] According to an embodiment of the present invention, the diffraction peaks representing LiTi2(PO4)3 include diffraction peak (012), diffraction peak (104), diffraction peak (113) and diffraction peak (024), and the 2θ values ​​corresponding to the above diffraction peaks are 14.685°, 20.843°, 24.491° and 29.641°, respectively. Therefore, compared with the 2θ values ​​corresponding to the standard spectrum, the above diffraction peaks are reduced by 0.02°-0.06°, which can further improve the ionic conductivity of the solid electrolyte material, so that the battery containing it has excellent rate performance.

[0058] According to an embodiment of the present invention, the unit cell parameter of the solid electrolyte material is increased compared with LiTi2(PO4)3. The c value increases That is, the unit cell parameters of the solid electrolyte material of the embodiment of the present invention are larger than those of the standard LiTi2(PO4)3. For example, the a value can be increased. etc., the c value can be increased As a result, the crystal of the solid electrolyte material of the embodiment of the present invention has larger unit cell parameters and unit cell volume than the standard LiTi2(PO4)3 crystal, thereby widening the transmission channel of lithium ions, improving the ion conductivity of the solid electrolyte material, and making the battery containing it have excellent rate performance.

[0059] According to an embodiment of the present invention, the unit cell volume of the solid electrolyte material is increased compared to the unit cell volume of LiTi2(PO4)3. For example As a result, the transmission channel of lithium ions is widened, the ionic conductivity of the solid electrolyte material can be improved, and the battery containing it has excellent rate performance.

[0060] According to an embodiment of the present invention, in the X-ray diffraction spectrum of the solid electrolyte material, there is a diffraction peak (721) at a diffraction angle 2θ value of 27.7°-27.8°, the peak intensity of the diffraction peak (721) is I1, the peak intensity of the diffraction peak (113) is I2, 0.1≤I1 / I2≤0.5, for example, I1 / I2 can be 0.1, 0.2, 0.3, 0.4, 0.5, etc. Specifically, the diffraction peak (721) is the diffraction peak of pyrophosphate, and the diffraction peak (113) is the diffraction peak of LiTi2(PO4)3. The peak intensity ratio of the two is controlled within the above range. Pyrophosphate is introduced into the unit cell of the LiTi2(PO4)3 structure, and the pyrophosphate content in the solid electrolyte material is moderate. The crystal unit cell parameters and unit cell volume of the solid electrolyte material are increased. This is because compared with phosphate, the pyrophosphate ion has more extranuclear electrons and a larger ion radius. Therefore, through pyrophosphate recombination, the unit cell parameters of the solid electrolyte are increased. As a result, the transmission channel of lithium ions is widened, which can improve the ionic conductivity of the solid electrolyte material, so that the battery containing it has excellent rate performance.

[0061] According to an embodiment of the present invention, the lattice distortion of the solid electrolyte material is in the range of 0.05%-0.5%, for example, it can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc. As a result, the transmission channel of lithium ions is widened, the ion conductivity of the solid electrolyte material can be improved, and the battery containing it has excellent rate performance.

[0062] According to an embodiment of the present invention, the ionic conductivity of the solid electrolyte material is greater than or equal to 5×10 -4 S / cm, for example 5×10 -4 S / cm, 1×10 -4 S / cm,5×10 -3 S / cm, 1×10 -3 S / cm,5×10 -2 S / cm, 1×10 -2 S / cm,5×10 -1 S / cm, 0.1S / cm, 1S / cm, 10S / cm, 100S / cm, etc. According to some other embodiments of the present invention, the ionic conductivity of the solid electrolyte material is greater than or equal to 1×10 -3 S / cm, the ionic conductivity of the solid electrolyte material is within the above range. The solid electrolyte material has high ionic conductivity, which is conducive to the rapid transmission of lithium ions, so that the battery containing it has excellent rate performance.

[0063] According to an embodiment of the present invention, the average particle size of the solid electrolyte material is 0.05μm-0.5μm, for example, 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, etc. According to some other embodiments of the present invention, the average particle size of the solid electrolyte material is 0.05μm-0.1μm. Controlling the average particle size of the solid electrolyte material within the above range can not only reduce the obstruction of lithium ion transmission caused by too small particle size, but also avoid the extension of the lithium ion transmission path caused by too large particle size of the solid electrolyte material, thereby improving the transmission speed of lithium ions and thus improving the rate performance of the battery.

[0064] According to an embodiment of the present invention, at 25°C, the pH value of the solid electrolyte material is 6-10, for example, 6, 7, 8, 9, 10, etc. Limiting the pH value of the solid electrolyte material to the above range can reduce the gas generation caused by the excessive acidity of the solid electrolyte. It can also improve the structural stability of the solid electrolyte material, reduce the impact of structural instability on ionic conductivity, and at the same time, allow the solid electrolyte material to have sufficient lithium to improve the purity and ionic conductivity of the solid electrolyte material.

[0065] According to an embodiment of the present invention, the solid electrolyte material comprises:

[0066] Li x M 1 y M 2 z Ti u (PO4) v1 (P2O7) v2 ,

[0067] Among them, M 1 Contains at least one of the first main group elements other than Li, M 2 At least one of the metal elements having positive trivalence, 1≤x<4, 0.1≤y≤0.5, 0.2 <z≤0.5,1<u≤5.5,2≤v1≤6,0.1<v2≤3。

[0068] As an example, x may be 1, 2, 3, 3.5, 3.9, etc.; y may be 0.1, 0.2, 0.3, 0.4, 0.5, etc.; z may be 0.2, 0.3, 0.4, 0.5, etc.; u may be 1.1, 2, 3, 4, 5, 5.5, etc., v1 may be 2, 3, 4, 5, 6, etc., and v2 may be 0.11, 0.5, 1, 2, 3, etc. According to some other embodiments of the present invention, M 1 including at least one of K, Rb and Cs; M 2 Includes at least one of V, La and Cr.

[0069] Thus, pyrophosphate is introduced into the unit cell of LiTi2(PO4)3 structure, and the v2 value is controlled, and the element M is introduced. 1 and M 2 , and control the y and z values, M 1 It can enter the lithium vacancies in the lattice and regulate the lattice defects of the solid electrolyte. 2 The atomic radius is large, and it can work together with pyrophosphate to further broaden the transmission channel of lithium ions. In summary, the solid electrolyte material adopts the substance with the above structural formula, and the ion conductivity is further improved, which is further beneficial to the rapid transmission of lithium ions and improves the rate performance of the battery containing it.

[0070] The solid electrolyte material has both phosphate and pyrophosphate as a skeleton, which can increase the unit cell size of the solid electrolyte, reduce the binding of carriers, and thereby increase the ionic conductivity of the solid electrolyte material and improve the rate performance of the battery.

[0071] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned solid electrolyte material. According to an embodiment of the present invention, the method comprises:

[0072] S100: M 2 Source, Ti source, PO4 3- Source, P2O7 4- The source, precipitant and solvent are mixed, and a precursor is obtained after co-precipitation and filtration.

[0073] According to an embodiment of the present invention, the M 2 Source, Ti source, PO4 3- Source, P2O7 4- The source, precipitant and solvent can be commercially available products.

[0074] As an example, the M 2 Sources include M 2 Oxides containing M 2 Phosphate, containing M 2 Sulfate, containing M 2 Chloride, containing M 2 Nitrate and M 2 at least one of the carbonates.

[0075] The Ti source includes at least one of a phosphate containing Ti, an acetate containing Ti, a sulfate containing Ti, a chloride containing Ti, a nitrate containing Ti, and a carbonate containing Ti.

[0076] The PO4 3-The source includes at least one of H3PO4, NH4H2PO4, (NH4)2HPO4, (NH4)3PO4, LiH2PO4, Li2HPO4, Li3PO4, NaH2PO4, Na2HPO4, and Na3PO4.

[0077] The P2O7 4- The source includes at least one of H4P2O7, (NH4)2H2P2O7, Li2H2P2O7, and Li4P2O7.

[0078] The precipitant includes at least one of sodium hydroxide, sodium carbonate and ammonia water.

[0079] According to an embodiment of the present invention, the solvent includes at least one of pure water, alcohols, and ethers.

[0080] S200: mixing the precursor with a Li source, M 1 The solid electrolyte material is obtained by mixing the raw materials and sintering them in an oxygen-containing atmosphere.

[0081] According to an embodiment of the present invention, the M 1 The L source and the Li source can be commercially available products.

[0082] As an example, the M 1 Sources include M 1 Oxides containing M 1 Phosphate, containing M 1 Sulfate, containing M 1 Chloride, containing M 1 Nitrate and M 1 at least one of the carbonates.

[0083] The Li source includes at least one of lithium carbonate, lithium hydroxide and lithium nitrate.

[0084] According to an embodiment of the present invention, the oxygen-containing atmosphere includes oxygen or air.

[0085] According to an embodiment of the present invention, the sintering temperature is 600°C-800°C, and the sintering time is 4h-10h. For example, the sintering temperature may be 600°C, 650°C, 700°C, 750°C, 800°C, etc.; the sintering time may be 4h, 5h, 7h, 9h, 10h, etc. The sintering temperature and time are controlled within the above ranges. Thus, by making the sintering temperature and time within the above ranges, a solid electrolyte material with higher purity and stable structure can be formed, thereby maintaining a higher ionic conductivity.

[0086] In the third aspect of the present invention, the present invention proposes a positive electrode active material, which includes a substrate and a coating layer arranged on at least a portion of the surface of the substrate, and the coating layer includes the solid electrolyte material described in the first aspect of the present invention or the solid electrolyte material prepared by the method described in the second aspect.

[0087] Thus, the surface of the positive electrode active material is coated with a solid electrolyte material, which introduces pyrophosphate into the unit cell of the conventional LiTi2(PO4)3 structure and doped with the element M 1 and M 2 , which increases the unit cell parameters and unit cell volume, thereby widening the lithium ion transmission channel. Coating the above-mentioned solid electrolyte material on the surface of the positive electrode active material can increase the lithium ion deintercalation rate in the positive electrode active material, improve the ionic conductivity of the positive electrode active material, and make the battery containing it have excellent rate performance.

[0088] In addition, since the solid electrolyte material has a higher ionic conductivity, the transfer rate of lithium ions at the interface between the positive electrode and the electrolyte is accelerated, so that the capacity and rate performance of the positive electrode active material are improved. At the same time, since the pyrophosphate has an oxygen vacancy compared to the phosphate, when the matrix of the positive electrode active material exhibits oxygen precipitation due to the participation of anions in the reaction, the pyrophosphate in the coating layer can anchor the active oxygen to generate phosphate, thereby maintaining the stability of the surface structure of the positive electrode active material and improving the cycle retention rate; at the same time, the strong oxidizing property of the positive electrode active material in the charged state is reduced, reducing battery gas production.

[0089] According to an embodiment of the present invention, the thickness of the coating layer is 10nm-500nm. For example, the thickness of the coating layer can be 10nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, etc. Therefore, by controlling the thickness of the coating layer within the above range, the ionic conductivity of the positive electrode active material caused by too low thickness of the coating layer can be reduced. The lithium ion transmission is blocked due to too high thickness of the coating layer, so that the ionic conductivity of the positive electrode active material is high, and the battery containing it has excellent rate performance.

[0090] According to an embodiment of the present invention, based on the total mass of the positive electrode active material, the mass proportion of the solid electrolyte material is 0.01%-1%. For example, the mass proportion of the solid electrolyte material can be 0.01%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1%, etc. The mass proportion of the solid electrolyte material is controlled within the above range, so that a coating layer of suitable thickness is formed on the surface of the substrate, so that the ionic conductivity of the positive electrode active material is high, and the battery containing it has excellent rate performance.

[0091] According to an embodiment of the present invention, in the DSC test curve of the positive electrode active material, the temperature corresponding to the exothermic peak is ≥ 220° C. For example, it can be 220° C., 230° C., 250° C., 300° C., 400° C., etc.

[0092] According to an embodiment of the present invention, the matrix includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, lithium manganese phosphate and lithium manganese iron phosphate, thereby, the prepared positive electrode active material has high ionic conductivity, so that the battery containing it has excellent rate performance.

[0093] According to an embodiment of the present invention, the gas generation of the soft-pack battery assembled with the positive electrode active material is ≤2 mL / Ah when stored at 60° C. for 7 days. It can be seen that the battery of the embodiment of the present invention generates less gas.

[0094] In a fourth aspect of the present invention, the present invention provides a method for preparing the positive electrode active material according to the third aspect, comprising:

[0095] S1: grinding the solid electrolyte material into nanoparticles and mixing them with a matrix to obtain a mixture;

[0096] S2: heat-treating the mixed material in an oxygen-containing atmosphere to obtain a positive electrode active material.

[0097] Thus, the positive electrode active material prepared includes a substrate and a coating layer provided on at least part of the surface of the substrate, wherein the coating layer includes the solid electrolyte material described in the first aspect of the present invention or the solid electrolyte material prepared by the method described in the second aspect. Thus, the surface of the positive electrode active material is coated with the solid electrolyte material, and the solid electrolyte material introduces pyrophosphate into the unit cell of the conventional LiTi2(PO4)3 structure, and the doping element M 1 and M 2 , which increases the unit cell parameters and unit cell volume, thereby widening the lithium ion transmission channel, which can improve the ionic conductivity of the solid electrolyte material and make the battery containing it have excellent rate performance.

[0098] According to an embodiment of the present invention, the oxygen-containing atmosphere includes oxygen or air.

[0099] The heat treatment can make the nanoparticle solid electrolyte material better attached to the surface of the substrate. According to an embodiment of the present invention, the temperature of the heat treatment is 300°C-500°C, and the time of the heat treatment is 2h-8h. For example, the temperature of the heat treatment can be 300°C, 350°C, 400°C, 450°C, 500°C, etc., and the time of the heat treatment can be 2h, 4h, 5h, 7h, 8h, etc. Within the above temperature and time range, it is beneficial to make the nanoparticle solid electrolyte material better attached to the surface of the substrate, improve the ionic conductivity of the positive electrode active material, and reduce the gas production of the battery containing it, so that the capacity and rate performance of the positive electrode active material are improved.

[0100] In a fifth aspect of the present invention, the present invention provides a positive electrode sheet. According to an embodiment of the present invention, the positive electrode sheet comprises the positive electrode active material described in the third aspect of the present invention, or the positive electrode active material prepared by the method described in the fourth aspect.

[0101] According to an embodiment of the present invention, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, the positive electrode active material layer includes the above-mentioned positive electrode active material, wherein the positive electrode collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode collector can be aluminum foil.

[0102] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0103] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0104] According to some embodiments of the present invention, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0105] It should be noted that the features and advantages described above for the positive electrode active material and the preparation method thereof are also applicable to the positive electrode plate and will not be described in detail here.

[0106] In a sixth aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery comprises at least one of the solid electrolyte material described in the first aspect of the present invention, the solid electrolyte material prepared by the method described in the second aspect, and the positive electrode sheet described in the fifth aspect.

[0107] As an example, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is located between the positive electrode sheet and the negative electrode sheet. During the charge and discharge process of the battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0108] According to an embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, wherein the negative electrode current collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode current collector can be a copper foil.

[0109] According to some embodiments of the present invention, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc.

[0110] According to some embodiments of the present invention, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0111] According to some embodiments of the present invention, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0112] According to some embodiments of the present invention, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0113] According to some further embodiments of the present invention, the negative electrode plate may include a metal lithium plate or a lithium alloy, such as a lithium-indium alloy.

[0114] According to some other embodiments of the present invention, there is no particular restriction on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. As an example, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular restriction. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular restriction.

[0115] According to some other embodiments of the present invention, the type of electrolyte is not specifically limited and can be selected according to needs. For example, the electrolyte can be in a gel state or a fully solid state. According to some specific embodiments of the present invention, the electrolyte is an electrolyte solution, and the electrolyte solution includes a lithium salt and a solvent.

[0116] According to some specific embodiments of the present invention, the lithium salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate or lithium tetrafluorooxalatophosphate.

[0117] According to some specific embodiments of the present invention, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone or diethyl sulfone.

[0118] In some embodiments of the present application, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0119] It should be noted that the above-mentioned features and advantages described for the positive electrode plate are also applicable to the solid-state battery and will not be repeated here.

[0120] In a seventh aspect of the present invention, the present invention provides an electric device. According to an embodiment of the present invention, the electric device includes the above-mentioned battery. According to an embodiment of the present invention, the electric device may include but is not limited to a mobile phone, a laptop computer, an electric vehicle, etc.

[0121] It should be noted that the features and advantages described above for the battery are also applicable to the electrical device and will not be repeated here.

[0122] Below, the embodiment of the present invention is described. The embodiment described below is exemplary, is only used to explain the present invention, and cannot be interpreted as limiting the present invention. If no specific technology or conditions are indicated in the embodiment, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0123] Example 1

[0124] Preparation of solid electrolyte materials:

[0125] Vanadium oxide, titanyl sulfate, disodium hydrogen phosphate, and titanium pyrophosphate were added according to a molar ratio of V 3+ :Ti 4+ :PO4 3- :P2O7 4- =0.3:2.7:4:0.5 in pure water, add precipitant sodium hydroxide, heat to 60°C and stir for 30 minutes to form a uniform precipitate, and obtain the precursor powder after filtering and drying.

[0126] The precursor, lithium carbonate and potassium carbonate are mixed according to Li + :K + :PO4 3- =2:0.3:4 in a ratio and mixed evenly in a high-speed mixer, sintered at 700° C. in air for 8 hours to obtain a micron-sized solid electrolyte material, the average particle size of the solid electrolyte material is 20 microns, and the pH value of the solid electrolyte material is 6.5 at 25° C.

[0127] The micron-sized composite oxide solid electrolyte material was added into pure water to prepare a slurry with a solid content of 50%. The slurry was milled with zirconium oxide balls in a ball mill for 6 hours to obtain a nano-slurry with an average particle size of less than 200 nm. The powder was treated by a spray dryer and then dissociated and sieved to obtain a relatively uniform particle size distribution with a composition of Li2K 0.3 V 0.3 Ti 2.7 (PO4)4(P2O7) 0.5 Solid electrolyte nanopowder.

[0128] Preparation of positive electrode active materials:

[0129] The obtained solid electrolyte nanopowder was mixed with LiNi 0.9 Co 0.05 Mn 0.05 The matrix of the positive electrode active material of O2 is weighed according to a mass ratio of 0.1:100 and mixed evenly in a high-speed mixer, and heat-treated at 400°C for 6 hours in an air atmosphere to obtain a positive electrode active material coated with a solid electrolyte.

[0130] The preparation methods of Examples 2 to 15 and Comparative Examples 1 to 4 are the same as those of Example 1, and the differences are detailed in Table 1.

[0131] Table 1

[0132]

[0133]

[0134] Preparation method of button cell: The positive electrode active material, solid electrolyte material, acetylene black and polyvinylidene fluoride (PVDF) prepared in each embodiment are mixed in a mass ratio of 90:2:3:5, coated on aluminum foil and dried, and stamped into a positive electrode sheet with a diameter of 12mm and a thickness of 120μm by a pressure of 100MPa, and then the positive electrode sheet is placed in a vacuum drying oven and dried at 120℃ for 12h. The negative electrode uses a Li metal sheet with a diameter of 17mm and a thickness of 1mm; the diaphragm uses a Celgard 2400 porous membrane with a thickness of 25μm; the electrolyte uses an equal amount of 1mol / L LiPF6, ethylene carbonate (EC) and diethyl carbonate (DEC). The positive electrode sheet, diaphragm, negative electrode sheet and 4μL electrolyte are assembled into a 2025 button cell in an Ar gas glove box with a water content and an oxygen content of less than 5ppm.

[0135] Performance Testing Methods

[0136] 1. Test method for ionic conductivity of solid electrolyte materials

[0137] The test method for ionic conductivity is to mold 5 mg of nanopowder of solid electrolyte material into a sheet sample at 200 MPa pressure in a steel mold with a diameter of 12 mm, and then place the molded sheet sample in a fixture to perform AC impedance test on an electrochemical workstation to obtain ionic conductivity.

[0138] 2. XRD test method

[0139] The X-ray diffraction test method is to use an X-ray automatic diffractometer to perform phase and crystal structure analysis, with an operating voltage of 40 kV, an operating current of 250 mA, continuous scanning, a scanning speed of 4° / min, a step size of 0.02°, and a scanning angle of 10°-80°.

[0140] The XRD patterns of the solid electrolyte materials of Examples 1-4 and Comparative Example 1 are as follows: Figure 1 and Figure 2As shown, it can be seen that compared with Comparative Example 1, the 2θ value of the diffraction peak representing LiTi2(PO4)3 of the solid electrolyte materials of Examples 1-4 is reduced compared with the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3, and the reduction angle is 0.02°-0.06°.

[0141] The scanning electron microscope image of the solid electrolyte material of Example 1 is as follows Figure 3 As shown, it can be seen that the solid electrolyte material is nanoscale, with an average particle size of about 200nm.

[0142] 3. Battery rate performance test method

[0143] The assembled battery was tested at 0.1C and 1C rates, and the ratio of the capacity at 1C rate to the capacity at 0.1C rate was calculated. The test results are shown in Table 2.

[0144] Table 2

[0145]

[0146] As can be seen from Table 2, in Examples 1-15 of the present application, the 2θ value of the diffraction peak representing LiTi2(PO4)3 in the X-ray diffraction spectrum of the solid electrolyte material is reduced by 0.02°-0.06° compared to the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3. However, the reduction in the 2θ value corresponding to Comparative Examples 1-4 is not within the range of 0.02°-0.06°, and the ionic conductivity of the solid electrolyte material of Comparative Examples 1-4 and the rate performance of the corresponding battery are significantly lower than those of Examples 1-15 of the present application. It can be seen that the present application controls the 2θ value of the diffraction peak representing LiTi2(PO4)3 in the X-ray diffraction spectrum of the solid electrolyte material, which is reduced by 0.02°-0.06° compared to the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3, thereby broadening the transmission channel of lithium ions, thereby improving the ionic conductivity of the solid electrolyte material, so that the battery containing it has excellent rate performance.

[0147] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0148] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A solid electrolyte material, characterized in that: The solid electrolyte material has a NASICON crystal structure. In the X-ray diffraction spectrum of the solid electrolyte material, the 2θ value of the diffraction peak representing LiTi2(PO4)3 is reduced by 0.02°-0.06° compared with the 2θ value of the corresponding diffraction peak in the standard spectrum of LiTi2(PO4)3; The solid electrolyte material comprises: Li x M 1 y M 2 z Tea u (PO4) v1 (P2O7) v2 , Among them, M 1 Contains at least one of the first main group elements other than Li, M 2 Including at least one of V, La and Cr, 1≤x<4, 0.1≤y≤0.5, 0.2 <z≤0.5,1<u≤5.5,2≤v1≤6,0.1<v2≤3。 2. The solid electrolyte material according to claim 1, characterized in that The diffraction peaks representing LiTi2(PO4)3 include diffraction peak (012), diffraction peak (104), diffraction peak (113) and diffraction peak (024).

3. The solid electrolyte material according to claim 1, characterized in that Compared with the unit cell parameters of LiTi2(PO4)3, the unit cell parameters of the solid electrolyte material are as follows: the a value increases by 0.002Å-0.006Å, and the c value increases by 0.01Å-0.03Å.

4. The solid electrolyte material according to claim 1, characterized in that The unit cell volume of the solid electrolyte material is 1Å larger than that of LiTi2(PO4)3. 3 -3Å 3 .

5. The solid electrolyte material according to claim 2, characterized in that: In the X-ray diffraction spectrum of the solid electrolyte material, there is a diffraction peak (721) at a diffraction angle 2θ value of 27.7°-27.8°, the peak intensity of the diffraction peak (721) is I1, the peak intensity of the diffraction peak (113) is I2, and 0.1≤I1 / I2≤0.

5.

6. The solid electrolyte material according to claim 1, characterized in that The ionic conductivity of the solid electrolyte material is greater than or equal to 5×10 -4 S / cm.

7. The solid electrolyte material according to claim 1, characterized in that The ionic conductivity of the solid electrolyte material is greater than or equal to 1×10 -3 S / cm.

8. The solid electrolyte material according to claim 1, characterized in that The average particle size of the solid electrolyte material is 0.05 μm-0.5 μm.

9. The solid electrolyte material according to claim 1, characterized in that The average particle size of the solid electrolyte material is 0.05 μm-0.1 μm.

10. The solid electrolyte material according to claim 1, characterized in that At 25° C., the pH value of the solid electrolyte material is 6-10.

11. The solid electrolyte material according to claim 1, characterized in that M 1 Includes at least one of K, Rb and Cs.

12. A method for preparing the solid electrolyte material according to any one of claims 1 to 11, characterized in that: include: M 2 Source, Ti source, PO4 3- Source, P2O7 4- The source, precipitant and solvent are mixed, and a precursor is obtained after co-precipitation and filtration; The precursor is mixed with a Li source, M 1 The solid electrolyte material is obtained by mixing the raw materials and sintering them in an oxygen-containing atmosphere.

13. The method according to claim 12, characterized in that The oxygen-containing atmosphere includes oxygen or air.

14. The method according to claim 12, characterized in that The sintering temperature is 600° C.-800° C., and the sintering time is 4 h-10 h.

15. The method according to claim 12, characterized in that The M 1 Sources include M 1 Oxides containing M 1 Phosphate, containing M 1 Sulfate, containing M 1 Chloride, containing M 1 Nitrate and M 1 at least one of the carbonates.

16. The method according to claim 12, characterized in that The M 2 Sources include M 2 Oxides containing M 2 Phosphate, containing M 2 Sulfate, containing M 2 Chloride, containing M 2 Nitrate and M 2 at least one of the carbonates.

17. The method according to claim 12, characterized in that The Ti source includes at least one of a phosphate containing Ti, an acetate containing Ti, a sulfate containing Ti, a chloride containing Ti, a nitrate containing Ti, and a carbonate containing Ti.

18. The method according to claim 12, characterized in that The PO4 3- The source includes at least one of H3PO4, NH4H2PO4, (NH4)2HPO4, (NH4)3PO4, LiH2PO4, Li2HPO4, Li3PO4, NaH2PO4, Na2HPO4, and Na3PO4.

19. The method according to claim 12, characterized in that The Li source includes at least one of lithium carbonate, lithium hydroxide and lithium nitrate.

20. The method according to claim 12, characterized in that The P2O7 4- The source includes at least one of H4P2O7, (NH4)2H2P2O7, Li2H2P2O7, and Li4P2O7.

21. The method according to claim 12, characterized in that The precipitant includes at least one of sodium hydroxide, sodium carbonate and ammonia water.

22. A positive electrode active material, characterized in that: It comprises a substrate and a coating layer provided on at least a part of the surface of the substrate, wherein the coating layer comprises the solid electrolyte material according to any one of claims 1 to 11 or a solid electrolyte material prepared by the method according to any one of claims 12 to 21.

23. The positive electrode active material according to claim 22, characterized in that The coating layer has a thickness of 10 nm to 500 nm.

24. The positive electrode active material according to claim 22, characterized in that Based on the total mass of the positive electrode active material, the mass proportion of the solid electrolyte material is 0.01%-1%.

25. The positive electrode active material according to claim 22, characterized in that In the DSC test curve of the positive electrode active material, the temperature corresponding to the exothermic peak is ≥220°C.

26. The positive electrode active material according to claim 22, characterized in that The matrix includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, lithium manganese phosphate and lithium manganese iron phosphate.

27. A method for preparing the positive electrode active material according to any one of claims 22 to 26, characterized in that: include: Grinding the solid electrolyte material into nanoparticles and mixing the nanoparticles with a matrix to obtain a mixed material; The mixed material is heat-treated in an oxygen-containing atmosphere to obtain a positive electrode active material.

28. The method according to claim 27, characterized in that The oxygen-containing atmosphere includes oxygen or air.

29. The method according to claim 27, characterized in that The temperature of the heat treatment is 300° C.-500° C., and the time of the heat treatment is 2 h-8 h.

30. A positive electrode plate, characterized in that: The invention comprises the positive electrode active material according to any one of claims 22 to 26, or the positive electrode active material prepared by the method according to any one of claims 27 to 29.

31. A battery, characterized in that: It comprises at least one of the solid electrolyte material described in any one of claims 1 to 11, the solid electrolyte material prepared by the method described in any one of claims 12 to 21, and the positive electrode sheet described in claim 30.

32. An electrical equipment, characterized in that: Comprising the battery of claim 31.

Citation Information

Patent Citations

  • Lithium titanium aluminum phosphate solid electrolyte, lithium ion battery and preparation method of lithium titanium aluminum phosphate solid electrolyte

    CN117246989A

  • Method for producing titanium pyrophosphate, and method for producing titanium pyrophosphate and solid electrolyte

    JP2020142973A

Cited By

  • Solid electrolyte material and preparation method therefor, positive electrode active material and preparation method therefor, positive electrode sheet, battery, and electric device

    EP4723272A1